(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aims to identify the impact of the COVID-19 pandemic on the financial performance of Saudi banks. The study utilizes the CAMELS rating system to identify aspects of the financial performance under it. The study compares two periods: the first is from the first quarter of 2017 to the fourth quarter of 2019 (the period prior to the pandemic), and the second period is from the first quarter of 2020 to the second quarter of 2021 (the pandemic period). The study depends mainly on secondary data published by Saudi Central Bank in its monthly bulletins, and it utilizes the empirical approach to test its hypotheses. The study results indicated that despite the unprecedented circumstances imposed by the pandemic on the Saudi economy during 2020, Saudi banks had adequate capital and enjoyed higher liquidity levels than in the period prior to the pandemic. The study results also indicated that the high rate of non-performing loans due to the adverse impact of the pandemic on the bank customers led to a deterioration in the quality of banks’ assets. Lastly, the study results indicated that a reduction in interest rates and an increase in loan allocations contributed to reducing the profitability of Saudi banks in the pandemic period compared to the period prior to the pandemic. The study offers a set of recommendations, the most important of which is Saudi banks have to prepare early for the risks related to corporate bankruptcy after the end of the loan repayment period specified by the Saudi Central Bank.